Application of a simple nonparametric conditional quantile function estimator in unemployment duration analysis - Laura Wichert; Ralf A. Wilke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
The paper analyses the potential impact of stock market developments on lending behaviour from different perspectives. First we scrutinize the impact of stock market movements on the banks? and on the borrowers? balance sheets. Subsequently we estimate aggregate credit supply and demand functions including a stock market indicator as explanatory variable. The analysis reveals no major importance of the bank balance sheet channel for the relationship between stock market volatility and corporate financing possibilities of non-financial companies. A possible impact of stock market movements on banks lending behaviour might be rooted in their impact on the balance sheets of corporate borrowers. The empirical results of the credit market analysis yield some confirming evidence for an impact of stock market developments. However, the results are not very stable and depend on the specification of the model and on the time period under observation.
More recent version: http://hdl.handle.net/10419/24617
Keywords: 330; Schätztheorie; Nichtparametrisches Verfahren; Mikroökonometrie; Arbeitslosigkeit; Dauer; Schätzung; Theorie; Deutschland